A database of noble gases in lunar samples in preparation for mass spectrometry on the Moon. (March 2020) - Curran, N.M.; Nottingham, M.; Alexander, L.; Crawford, I.A.; Füri, E.; Joy, K.H.
Abstract: The lunar regolith provides a temporal archive of the evolution of the Moon and inner Solar System over the last ~4 billion years. During this time, noble gases have been trapped and produced within soils and rocks at the lunar surface. These noble gas concentrations can be used to unravel the history of lunar material and shed light on processes that have evolved the surface of the Moon through time. We have collected published noble gas data for a range of lunar samples including soils, regolith breccias, crystalline (e.g., mare basalts, anorthosite) and impact-melt rocks. The compilation includes noble gas concentrations and isotope ratios for He, Ne, Ar, Kr and Xe; trapped, cosmogenic and radiogenic isotopes; and cosmic ray exposure ages. We summarise the significance of these data, which can be used as a baseline for expected noble gas concentrations in a range of lunar samples, and provide a framework for future in situ noble gas measurements on the lunar surface. Highlights: Published lunar sample noble gas data is collated, including: soils, regolith breccias, crystalline and impact-melt rocks. The data include: He, Ne, Ar, Kr and Xe gas concentrations, isotope ratios, component fractions and cosmic ray exposure ages. We summarise the significance of these data, and provide a framework for future in situ noble gas measurements on the lunar surface.